Challenges of the University of Maribor in the Areas of European Integration, Micro-Credentials, Digitalisation and the Green Transition - Kačič, Zdravko; Mongus, Domen; Golob, Izidor; Vlaovič, Boštjan; Frumen, Sebastijan; Ješovnik, Anita (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2026)
The third decade of the Bologna Process will be largely focused on the institutionalisation of the Common European Higher Education Area (EHEA). With the adopted University of Maribor Strategy 2021-2030, the university follows the most important guidelines of the Bologna Process. As a partner of the European Alliance ATHENA, it actively participates in the shaping of the EHEA. At the university, as part of the implementation of the Recovery and Resilience Plan (RRP) pilots, we are developing numerous pilot short courses. In the field of green transition, the university is successfully implementing 23 RRP pilot projects to ensure sustainable operations. The university is ahead of a building infrastructure investment cycle, which will involve twelve faculties over the next five years. The university is aware of the challenges posed by the development of artificial intelligence tools. Through its research work, it acts as a developer of artificial intelligence tools, while at the same time developing a culture of responsible use of artificial intelligence. By developing and implementing the INNOVUM platform, the university aims in the field of knowledge transfer to make a significant contribution to building the foundations for the development and innovation breakthrough of the Eastern Slovenia Cohesion Region.